Study of an interesting physical mechanism of memory effect in nematic liquid crystal dispersed with quantum dots. Issue 5 (9th April 2019) - Rastogi, Ayushi; Agrahari, Kaushlendra; Pathak, Govind; Srivastava, Atul; Herman, Jakub; Manohar, Rajiv
ABSTRACT: The present study is based on effect of dispersing Cd1 −x Znx S/ZnS core/shell quantum dots (QDs) on the memory behaviour of nematic liquid crystal 2020 with the variation of dopant concentration and applied voltage. Around 26% and 45% memory storage in QDs dispersed nematic matrix (MIX 1 and MIX 2) has been the core finding. The presence of ionic charges at low-frequency regime along with their reduction in QDs dispersed nematic matrix has been confirmed from tan δ curve. Pure nematic LC as well as nematic/QD mixtures depict volatile memory effect that depends upon concentration of QDs. The existence of memory due to storage of charge on QDs has been further confirmed from the dielectric, polarising optical micrographs and electro optical study under the influence of bias voltage. The observation of memory effect is attributed to the ion capturing and ion releasing phenomenon. The dispersion of QDs in nematic material plays an important role to enhance memory parameter by capturing and releasing the ionic charges under the application of bias voltage which has been confirmed from capacitance-voltage curve. Graphical Abstract: